Pengaruh Flash Sale dan Gratis Ongkos Kirim terhadap Keputusan Pembelian Konsumen pada Marketplace Shopee di Masyarakat Kabupaten Dompu - Suhada Suhada; Yeye Suhaety; Desi Rubiyanti (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the effect of flash sales and free shipping on consumer purchasing decisions on the Shopee marketplace in Dompu Regency. This study uses a quantitative approach with a survey method. The study population is all active Shopee users in Dompu Regency whose number is not known for certain. The sample size was determined using the Lemeshow formula to obtain 96 respondents, while the sampling technique used purposive sampling. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with the help of SPSS. Before testing the hypothesis, the data were tested through validity, reliability, normality, multicollinearity, and heteroscedasticity tests. The results showed that flash sales have a positive and significant effect on consumer purchasing decisions with a regression coefficient value of 0.424 and a significance value of 0.000. Free shipping also has a positive and significant effect on purchasing decisions with a regression coefficient value of 0.504 and a significance value of 0.000. Simultaneously, flash sales and free shipping have a significant effect on purchasing decisions with a calculated F value of 248.542 and a significance value of 0.000. The Adjusted R Square value of 0.839 indicates that the two variables can explain 83.9% of the variation in consumer purchasing decisions. This finding indicates that promotional strategies such as flash sales and free shipping are important factors influencing consumer purchasing decisions on the Shopee marketplace Dompu Regency.